Multiple levels and multiple challenges for measurement, reporting and verification of REDD+ - Korhonen-Kurki, Kaisa; Brockhaus, Maria; Duchelle, Amy E.; Atmadja, Stibniati; Pham Thu Thuy; Schofield, L. (Ubiquity Press, Ltd., 2013)
REDD+ is a multilevel endeavour. Global demands, national and subnational structures and local people's needs and aspirations must all be linked in efforts to reduce emissions from deforestation and forest degradation. We use Brockhaus and Angelsen's (2012) framework of Institutions, Interests, Information and Ideas (4Is) to analyse the multilevel governance of REDD+ through one of its core elements: measurement, reporting and verification. We present the multilevel dimensions of REDD+ and the risks if they are disregarded. We analyse the flow and interplay of information, institutions and interests across levels in REDD+ measurement, reporting and verification and examine which multilevel governance mechanisms enable this flow. To support our analysis, we provide anecdotal evidence of challenges and opportunities from three countries: Brazil, Vietnam and Indonesia. Our analysis shows that it is essential to enhance and harmonize information flows between local and national levels for measurement, reporting and verification to be accountable. Furthermore, sound information flows between levels can increase the negotiation power of disadvantaged groups and ensure a more effective, efficient and equitable REDD+. To reduce the risk of conflict, REDD+ multilevel governance systems must match incentives and interests with transparent institutions. Effective multilevel governance mechanisms, such as novel cross-scale institutional arrangements, uniform regulations on the rights, responsibilities and procedures for monitoring information flows, and participation across levels, will provide tools for both information flow and greater matching of different interests across levels..